Museo de Arte Abstracto Español : Fundación Juan March - Bonet, Juan Manuel; Maderuelo, Javier (Madrid : Editorial de Arte y Ciencia, 1997)
Owned and managed by the Fundación Juan March, the Museum of Spanish Abstract Art in Cuenca houses a permanent exhibition of 110 paintings and sculptures by Spanish artists. A selection of 56 works by 30 artists are reproduced and analyzed in this catalogue, which also includes a short history of the Museum and a description of the artistic movement and the different generations represented in the collection. Written by the art historians and critics Juan Manuel Bonet and Javier Maderuelo, the catalogues offers a comprehensive vision of twentieth-century Spanish abstract art through the work of some of its most representative figures.
Basterretxea, Nestor ; Camin, Joaquin Rubio ; Canogar, Rafael ; Chillida, Eduardo ; Chirino, Martin ; Cuixart, Modest ; Delgado, Guillermo ; Farreras, Francisco ; Feito, Luis ; Gabino, Amadeo ; Guerrero, José ; Hernandez Pijuan, Juan ; Lorenzo, Antonio ; Manrique, César ; Millarès, Manuel ; Mompo, Manuel H. ; Munoz, Lucio ; Oteiza, Jorge ; Palazuelo, Pablo ; Rivera, Manuel ; Rueda, Gerardo ; Saura, Antonio ; Sempere, Eusebio ; Serrano, Pablo ; Teixidor, Jordi ; Torner, Gustavo ; Tàpies, Antoni ; Viola, Manuel ; Yturralde, Jose Maria ; Zobel, Fernando
biog. per kunstenaar
Engels & Spaans
boek
Keywords: Spanje; Cuenca